2008
DOI: 10.22358/jafs/66598/2008
|View full text |Cite
|
Sign up to set email alerts
|

The tissue-specific and developmental expression patterns of the forkhead transcription factor FoxO1 gene in pigs

Abstract: The forkhead transcription factor FoxO1 has been studied as the most downstream targets of the signaling pathway in mammals, and played a key role in adipogeneic, cell cycle progression, and energy metabolism and so on. The aim of this study was to investigate the tissue-specifi c and weight-dependent expression patterns of FoxO1 gene in porcine omental adipose tissue and its relation to adipose deposition. Sixty female Duroc × Landrace × Yorkshire pigs in 5 groups, each group containing twelve pigs weighing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, Liu et al (2008) showed that FoxO1 mRNA was expressed at a lesser level in the duodenum of pigs. This implied that FoxO1 may have a post-transcriptional regulatory mechanism in the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Liu et al (2008) showed that FoxO1 mRNA was expressed at a lesser level in the duodenum of pigs. This implied that FoxO1 may have a post-transcriptional regulatory mechanism in the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous works have already demonstrated that FoxO4 is a primary forkhead transcriptional factor localized in the gastrointestinal tracts of the pig , particularly in the duodenum (the most critical nutrient-absorbing organ). Besides, Liu et al (2008) have found that FoxO1 mRNA is expressed at a lesser level in the duodenum, subcutaneous adipose tissue, and pancreas when compared with other tissues of pigs. Also, the expression level of the FoxO1 gene was the lowest in the pigs at 20 kg.…”
Section: Introductionmentioning
confidence: 92%